2017
DOI: 10.5430/ijhe.v6n4p122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ICT Skills on the Job Satisfaction of Teacher Educators: Evidence from the Universities of the Sindh Province of Pakistan

Abstract: This research paper is a reflection of the results of collected data from Teacher Educators (TEs) regarding their skills and expertise in Information and Communication Technologies (ICT). Seven themes were inductively identified and called, 7Es like as: (a). Expertise in use of windows programmes; (b). Expertise in use of security measures; (c). Expertise in use of hardware instruments; (d). Expertise in use of internet; (e). Expertise in creating accounts; (f). Expertise in installation of softwares; and (g).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 62 publications
4
36
0
Order By: Relevance
“…Another research conducted by Okoli (2018) who conducted research at some Private Universities in Nigeria, where the results of his research found that the job satisfaction of academic staff in private universities is strongly influenced by the climate of the campus organization. The same results at the university level were also found by Sahito and Vaisanen, (2017), who conducted research at several universities in Pakistan, where the organizational climate affected the satisfaction of lecturers at the college. At the level of basic education, research conducted by Treputtharat and Tayiam (2014) in several primary schools in Thailand shows that the organizational climate in schools has a significant influence on job satisfaction of teachers.…”
Section: The Contribution Of School Climate To Teacher Job Satisfactisupporting
confidence: 76%
“…Another research conducted by Okoli (2018) who conducted research at some Private Universities in Nigeria, where the results of his research found that the job satisfaction of academic staff in private universities is strongly influenced by the climate of the campus organization. The same results at the university level were also found by Sahito and Vaisanen, (2017), who conducted research at several universities in Pakistan, where the organizational climate affected the satisfaction of lecturers at the college. At the level of basic education, research conducted by Treputtharat and Tayiam (2014) in several primary schools in Thailand shows that the organizational climate in schools has a significant influence on job satisfaction of teachers.…”
Section: The Contribution Of School Climate To Teacher Job Satisfactisupporting
confidence: 76%
“…Teachers, who feel satisfied with their job, work in a positive school climate, get motivated by their top managers and share common values and culture with their colleagues, tend to use CMSs more effectively. Study findings on job satisfaction and classroom management show that satisfied teachers use CMSs better and also teachers who use CMSs effectively get satisfied with their jobs (Bilač, & Miljkovic, 2017;Sahito & Vaisanen, 2017). Another dimension is school climate which is multi-dimensional and influences all stakeholders such as students, parents and school personnel (Marshall, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is very likely that both crowd learning and internet social learning research will impact on and affect current educational models as a whole. Indeed, although there are some who argue that the process of pedagogy will remain the same (Kalantzis, 2006;Kalantzis & Cope, 2008), many authors are persuaded that educational processes will change according to the new learning opportunities and modalities (Khapaeva & Genči, 2016;Sahito & Vaisanen, 2017). New learning paradigms that involve intelligent programs and smart devices will lead towards new forms of relationships and, accordingly, towards to a new generation of educational models.…”
Section: Resultsmentioning
confidence: 99%